Development of pressure sensors for smart textiles - Gomes, Pedro (2018)
The investigation of textile sensors has increased and has gained an important role in the creation of new solutions for the most varied products, from monitorization sensors, actuators and controllers, implemented in garments, house textile items, or textiles structures used for a specific purpose e.g. bridge structural monitoring, soil proprieties, among others. This paper presents the development of pressure sensors base in a conductive silicone with piezoresistive conductive properties. The objective is to explore the combination of different types of conductive material (conductive silicon, nonconductive silicon, conductive ink and conductive fabric) and test the interactions between them. In the production methods the conductive ink, and conductive fabric were fixed to the silicone in the curing phase. Conductive and nonconductive silicon were mixed to obtain better control of sample conductivity. Samples with different thicknesses were developed, it was study the influence on the voltage variation and conductivity for each sample.